APLIKASI E-KINERJA SEBAGAI MONITORING KERJA DAN PENILAIAN KARYAWAN DI LEMBAGA PENJAMIN MUTU PENDIDIKAN (LPMP) JAMBI : Performance;Reports;Applications;Employees;Monitoring. - Sany, Ezrifal (LP2M Universitas Nurdin Hamzah, 2021)
The process of controlling and managing activities or work must be carried out to get maximum results in achieving the desired targets, so that supervision from the leadership is needed in controlling work activities carried out by employees so that the desired results are in accordance with the needs. target company or agency. One way this is done is by viewing and assessing reports on the results of employees' work each month whether the reports are accepted or not. If the report is rejected, employees must correct it in accordance with the work contained in their respective main duties and functions, and if the report is received, verification will be carried out from the supervisor and the report will be stored in the activity file. cabinet. Judging from the above activity process, the process will be carried out continuously and requires quite a lot of archive shelves, so that it is a problem that occurs today. Archives that are stored are also prone to being damaged and lost so that if needed, the archives needed are damaged or lost so that it is very troublesome in the process of carrying out their activities.